Duodenal tumor risk in Lynch syndrome. Issue 2 (February 2019) - Hammoudi, Nassim; Dhooge, Marion; Coriat, Romain; Leblanc, Sarah; Barret, Maximilien; Bordacahar, Benoit; Beuvon, Frederic; Prat, Frederic; Maksimovic, Fanny; Chaussade, Stanislas
Abstract: Background and aims: Lynch syndrome (LS) is associated with an increased risk of small bowel tumors but routine screening is not recommended in international guidelines. The aim of our study was to determinate the prevalence of duodenal tumors in a French cohort of LS patients. Methods: Patients carrying a germline pathogenic variant in a MMR gene, supported by our local network, in which at least one upper endoscopy had been performed, were included. We registered the occurrence of duodenal lesions in those patients. Results: 154 LS patients were identified including respectively 85 MSH2 and 41 MLH1 mutated patients respectively. Seven out of 154 (4.5%) had at least one duodenal lesion. Median age at diagnosis was 58 years (range: 49–73). The twelve lesions locations were: descending duodenum (n = 7), genu inferius (n = 2), duodenal bulb (n = 1), ampulla (n = 1), fourth duodenum (n = 1). Three lesions were invasive adenocarcinomas. The incidence rate of duodenal lesions in patients with MSH2 or MLH1 pathogenic variants was respectively 7.1% (6 out of 85) and 2.4% (1 out of 41) emphasizing a trend toward increased risk of developing duodenal lesion in MSH2 mutated patients: OR: 5.17, IC95% (0.8–60.07), p = 0.1307. Conclusion: Regarding this high prevalence rate, especially in MSH2 patients, regular duodenal screening during upper endoscopy should be considered in routine in LS patients.